Features of preparing children of the seventh year of life for writing - Shchapova E. V., Galkina I. A. (Interactive science, 2024)
The article describes the process of mastering writing by children of senior preschool age
Keywords: язык; грамота; письмо; дошкольный возраст; Language; preschool age; writing; literacy